The systematic medical appraisal, referral and treatment (SMART) mental health programme: Formative research informing a cluster randomized controlled trial - Mercian Daniel; Amanpreet Kaur; Ankita Mukherjee; Amritendu Bhattacharya; Abha Tewari; Rajesh Sagar; Shashi Kant; David Peiris; Pallab K. Maulik (Elsevier, 2023)
Background: Gaps exist between prevalence and treatment options for mental disorders in India. Limited awareness, poor help-seeking, scarcity of trained mental health professionals, limited mental health services and stigma are few examples of reasons contributing to treatment gap. Aims: This paper highlights findings from formative research of a primary mental healthcare model comprising of a preliminary feasibility testing of the Electronic Decision Support System (EDSS) to provide care using mobile based applications, perceptions of the community towards mental health and incorporating cultural adaptations for pre-existing anti-stigma campaign materials. Methods: A cross-sectional mixed methods approach tested the user acceptability of the electronic decision support system EDSS for accredited social health activists (ASHAs) and Primary Health Centre (PHC) doctors using tablets in two villages and two PHCs in rural Haryana (Northern India). Five focus groups and six in-depth interviews along with non-participant observations were used to ascertain community perceptions about various aspects related to mental health. Findings of the study were analyzed and interpreted against the key themes of Andersen's model. Results: Out of a total of 553 individuals screened for common mental disorders, 51 (9.2%) were screened positive and 32 visited PHC doctors for treatment. There was limited knowledge about common mental disorders amongst community; need to train primary health workers to identify and treat mental disorders; and incorporate cultural adaptation of anti-stigma awareness materials. Conclusions: The EDSS was found to be acceptable and feasible by primary and community health workers. The findings guided refining of the intervention prior to implementation of a large-scale cluster randomized controlled trial.